El habeas corpus a personas privadas de libertad con sentencia ejecutoriada y su alcance en el Sistema de Rehabilitación Social. - Manzano Núñez, Jhoanna Elizabeth (2023)
The present investigative work focuses its analysis on habeas corpus to persons deprived of Liberty with an enforceable sentence and its scope in the Social Rehabilitation System through a doctrinal and legal study on the application of this jurisdictional guarantee, the study of sentences, as well as also the analysis of the purposes of the Social Rehabilitation System and the rights of persons deprived of Liberty. The research is fundamental, bibliographic documentary, field, analytical and descriptive of non-experimental design, carried out on a population of 47 people. As a research technique, the survey and the interview were used. As an instrument, the questionnaire has made it possible to establish the scope of the habeas corpus action in the Social Rehabilitation System. Hence, at the end of the work, we have concluded that the habeas corpus action does not distinguish whether the persons deprived of Liberty have an enforceable sentence. Its only objective is the protection of the Liberty, life, and physical integrity of the persons deprived of Liberty; thus, it has been possible to demonstrate its scope in the Social Rehabilitation System, the lack of action on the part of the State and its delegates has caused this system to not fulfill its established purposes, which is why several prisoners with final sentences have made use of this jurisdictional guarantee to protect his life and the judges have given way to this action.